2010
DOI: 10.1007/s12529-010-9129-2
|View full text |Cite
|
Sign up to set email alerts
|

Care or Not Care—that is the Question: Predictors of Healthcare Utilisation in Relation to Employment Status

Abstract: Unemployment is a risk factor for both contacting a physician and for unmet care needs. A low social network and economic hardship are more present among persons who abstain from seeking healthcare and seem to be more common among the unemployed. The healthcare system should also be aware of the fact that some unemployed people with symptoms of depression abstain from seeking care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…A recent Swedish study has demonstrated that unemployment has a large impact on healthcare-seeking behaviour [29]. However, due to statistical power issues, it is not possible to conduct similar analyses in this study.…”
Section: Methodological Problemsmentioning
confidence: 88%
“…A recent Swedish study has demonstrated that unemployment has a large impact on healthcare-seeking behaviour [29]. However, due to statistical power issues, it is not possible to conduct similar analyses in this study.…”
Section: Methodological Problemsmentioning
confidence: 88%
“…These indicate an association between higher rates of forgone care and female gender, younger age, rural living area, unemployment, low educational level, low income and poor health [4,9,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[25] Social support may improve the accessibility of health care. [8] In this case, the Project employer’s referral probably encouraged participation in the work ability assessment because “everybody else was taking part as well”. [26] The health care systems should recognise the fact that some unemployed people abstain from seeking care.…”
Section: Discussionmentioning
confidence: 99%
“…[26] The health care systems should recognise the fact that some unemployed people abstain from seeking care. [8]…”
Section: Discussionmentioning
confidence: 99%